A New 5-Point Ternary Interpolating Subdivision Scheme and Its Differentiability. (11th November 2012) - Mustafa, Ghulam; Irum, Jayyada; Bari, Mehwish
Abstract : A new 5-point ternary interpolating scheme with a shape parameter is introduced. The resulting curve isC 2 for a certain range of parameters. The differentiable properties of the proposed scheme to extend its application in the generation of smooth curves are explored. Application of the proposed scheme is given to show its visual smoothness. The scheme is also extended to a 5-point tensor product ternary interpolating scheme, and its numerical examples are also included.